Therapeutic Drug Monitoring for Evaluation of the Efficacy and Safety of Vancomycin in Patients with Orthopaedic Infections - O. S. Tufanova; A. R. Kasimova; S. A. Bozhkova (Безопасность и риск фармакотерапии, 2022)
Vancomycin is a drug of choice for the infections caused by methicillin-resistant strains of staphylococci. Its use requires individualised dosing and renal function monitoring.The aim of the study was to evaluate, using therapeutic drug monitoring (TDM), the frequency of reaching target trough serum concentrations (TSCs) and the frequency of renal function impairment in orthopaedic infection patients receiving vancomycin therapy.Materials and methods: the authors carried out a retrospective analysis of vancomycin TSC test results of 457 patients admitted to a purulent osteology department in 2019–2021. The results were grouped according to the number of TSC determination performed as part of TDM (tests 1, 2, and 3). Each of the 3 groups was further divided into 4 subgroups according to the TSCs of vancomycin: ≤9.9 µg/ml (extremely low), 10–14.9 µg/ml (recommended for mild infections), 15–19.9 µg/ml (recommended for bone and joint infections), ≥20 µg/ml (potentially toxic). The results obtained in each group were analysed separately.Results: according to the 1st TDM test, only 9.6% of patients achieved the TSCs of vancomycin recommended for bone and joint infections. Extremely low TSCs, insufficient for treatment of the infections, were found in 64.8% of patients. According to the 2nd and 3rd TSC determinations, dose corrections decreased the percentage of patients with extremely low TSCs to 49.9% and 41.2%, respectively. Potentially toxic TSCs of vancomycin were detected in 48 (10.5%) patients, but renal dysfunction was observed only in 8 (1.75%) of them. The authors exemplify the use of TDM to control the efficacy and safety of vancomycin in patients with pronounced signs of renal function impairment by two clinical cases.Conclusion: with a standard dose of vancomycin, the concentrations recommended for bone and joint infections were reached only in every tenth patient. There was a large percentage of patients with extremely low serum concentrations of the medicinal product (64.8%), but it decreased after dose adjustments. Monitoring of vancomycin concentrations allows for individualised dosing, efficacy control and significant reduction of the risk of adverse kidney reactions.